Interleukin-1 involved in Apoptosis of Beta-Thalassemia/Hemoglobin E Erythroid Progenitor Cells - Gupta, Umesh Prasad; Fucharoen, Pranee; Tanyong, Dalina I (Asian Journal of Medical Sciences, 2013)
Objective: The major pathophysiological features of β-thalassemia are anemia and ineffective erythropoiesis. Ineffective erythropoiesis has been shown by an intense marrow erythroid hyperplasia and increased apoptosis during basophilic to orthochromatic normoblast stages. Some cytokines like interferon-γ (IFN-γ), tumor necrosis factor α (TNF-α) and interleukin-1 (IL-1) have been found to involved in apoptosis. Although the pro-apoptotic activity of IFN-γ and TNF-α is well documented, there are only few studies on IL-1, especially on erythroid lineage. In this in vitro study, the role of cytokine IL-1α and IL-1β in apoptosis of erythroid progenitor cells from β- thalassemia/HbE patients was assessed. Methods: Erythroid progenitor cells were isolated from peripheral blood of healthy subjects and β-thalassemia/HbE patients. Cells were then cultured, with and without 20 ng/ml IL-1α and IL-1β. Total cells and percent cell viability were performed by using trypan blue staining. Percent cell apoptosis was analyzed by using flow cytometer. Results: Both IL-1α and IL-1β were significantly decreased erythroid progenitor cells. IL-1 at 20 ng/ml reduced the glycophorin A positive cells and percent cell viability of erythroid progenitor cells from β-thalassemia/HbE patients, while there was increased apoptosis in this group. The highest percent apoptosis was observed in 20 ng/ml IL-1β treated β-thalassemia/HbE erythroid progenitor cells. Conclusion: IL-1β could be involved in apoptosis of erythroid progenitor cells from β-thalassemia/HbE patients which might be related with ineffective erythropoiesis of the disease. DOI: http://dx.doi.org/10.3126/ajms.v3i4.6805 Asian Journal of Medical Science Vol.3(4) 2012 pp.8-14